Anatomic Predilection of Isocitrate Dehydrogenase-Mutant Gliomas: A Multi-Institutional Spatial Analysis - Park, Minjun; Weiss, Hannah; Harake, Edward S.; Fang, Camila; Springer, Alex; Goff, Nicolas K.; Markert, John E.; Reinecke, David; Maarouf, Nader; Heiland, Dieter Henrik; Miller, Alex M.; Hollon, Todd; et al. (Neurosurgery, 2026)
BACKGROUND AND OBJECTIVES: – Interactions between cancer cells and their microenvironment are central to tumor formation. Regional microenvironmental variability in the brain may offer insights into essential factors in tumorigenesis. Surprisingly, a granular assessment of regional patterns of gliomagenesis has not been undertaken in the molecular era. The aim of this study was to quantitatively establish the anatomic distribution of the major molecular subtypes of adult diffuse glioma.METHODS: – We retrospectively analyzed 204 isocitrate dehydrogenase (IDH)-mutant and 200 IDH-wildtype gliomas. Reproducibility was assessed in an external cohort (190 IDH-mutant, 227 IDH-wildtype), and microarray expressions from Allen Human Brain Atlas were used to compare transcriptomic profiles between IDH-mutant hotspots and coldspots.RESULTS: – A total of 50.5% (103/204) of IDH-mutant tumors arose with the superior and middle frontal gyri, indicating a 3.1-fold regional enrichment relative to the volume of these gyri (P < .001). Totally, 9.5% (19/200) of IDH-wildtype tumors arose in the superior temporal gyrus with a 2.1-fold enrichment (P = .01). IDH-mutant and wildtype tumors were enriched by 4 and 4.5-fold, respectively, in the insula (both P < .001). Overall, 23.3% (24/103) of astrocytomas occurred disproportionately higher in the insula compared with oligodendrogliomas (P < .001). Transcriptomic analysis comparing the lobar hotspot (frontal lobe) to the coldspot (occipital lobe) revealed frontal enrichment of cholesterol (normalized enrichment score = 1.78) and fatty acid (normalized enrichment score = 1.94) metabolism pathways, paralleling the observed regional enrichment of IDH-mutant gliomas.CONCLUSION: – This study identifies molecular subtype-specific glioma hotspots and may suggest that regional metabolic differences may underlie the brain's variable vulnerability to gliomagenesis. These findings provide a framework for investigating additional microenvironmental factors that drive human glioma formation.
CRIS-Team Scopus Importer:2026-04-17
Keywords: Astrocytoma; Gliomagenesis; IDH-mutant; Oligodendroglioma; Superior frontal gyrus